Accident Study and Analysis of Selected Black Spots – A Case Study - Singh, Sandeep; ., . (International Journal of Engineering and Technology, 2018)
In the present study, accident statistics of 2011 to 2014 has resolved Vidya path as a black spot. In addition, attempt has been made to investigate the prevailing conditions of two V3 road stretches i.e. (Stretch – 1: road dividing sec – 14 and 15 and Stretch – 2: road dividing sec – 11 and 12) of Chandigarh for accidental risk. The moral of investigation has cleared that all the prime associated parties i.e. traffic, speed and users/driver are favoring the accidental risk; as during peak hour the road stretches were found short of capacity, speed of vehicles was over the legal speed and the users were ignoring the rules and regulation of driving. Consequently, the injury and life risk for pedestrians and cyclists are at the most. The preventive measures for the same are also incorporated.